PENGEMBANGAN MEDIA CAREER FLASHCARD TERHADAP PERENCANAAN KARIER SISWA DI SMPN 3 NGAMPRAH - Nugraha; Hendriana, Heris; Masyita Suherman, Maya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Inaccuracies in the career planning of students can cause failure in the future, if the work they get is considered not in accordance with their type or personal style, it will cause discomfort at work, and in the end it will end up being an increase in unemployment in Indonesia. Therefore the need for career planning that is done early on. One of the media that can be used in planning a student's career at school is a media career flashcard which is packaged in the form of a fun game. This study was conducted to determine the feasibility of career flashcard media in career guidance services. This research is a development research (RnD) which was carried out with several validation tests, namely by conducting validation tests on experts and limited trials to 10 students and broad testing to 40 students of class VIII-I at SMPN 3 Ngamprah. The assessment of the suitability of the career flashcard media was carried out by the validator and carried out a limited and extensive test with the final result of the career flashcard product validity test being 94.46% which was included in the "very suitable for use" category after revising. From the development of the career flashcard media product that was made in carrying out career planning for class VIII students at SMPN 3 Ngamprah. With career guidance services using career flashcard media, it was found that students opened their horizons in planning future careers that were tailored to their personality type.